Ciliary Neurotrophic Factor (CNTF) affects the excitable and contractile properties of innervated skeletal muscles - BEATRIZ U RAMIREZ; LEIRA RETAMAL; CECILIA VERGARA (Biological Research, 2003)
The well-established trophic role of CNTF upon neurons led to performing clinical trials in patients of neurodegenerative diseases. However, trials were suspended due to side effects such as severe weight loss, hyperalgesia, coughing, muscle cramps and pain. So far it is not known how CNTF triggers the problems related to skeletal muscle cramps and pain. CNTF has also been described as a myotrophic factor for denervated skeletal muscles, but the possibility that it affects innervated muscles has also been considered. Since a myotrophic factor could be a valuable tool for treatment of several muscle diseases, we studied the effects of low doses of CNTF delivered systemically by an osmotic pump, over the electrical and mechanical properties of innervated and denervated fast and slow muscles. CNTF induced spontaneous electrical discharges and slowed twitches in innervated muscles, but did not prevent the changes induced by denervation. We postulate that the spontaneous discharges induced by CNTF in innervated muscles may be the cause of the cramps, coughing, and muscle ache reported by patients. At low doses, CNTF does not exert its myotrophic role over denervated muscles but clearly affects the excitable and contractile properties of innervated muscles.